2012
DOI: 10.1017/s1352465812000847
|View full text |Cite
|
Sign up to set email alerts
|

Worry and Rumination in Anorexia Nervosa

Abstract: The data suggest that worry and rumination are major concerns for this group and warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
75
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 43 publications
13
75
1
3
Order By: Relevance
“…This puts our findings in line with previous research, having found that worry and rumination are associated with eating disorder symptoms (Startup et al, 2013;Sternheim et al, 2012). Earlier studies have shown that eating disorder symptoms correlated significantly with worry (Sternheim et al, 2012), and rumination (Startup et al, 2013).…”
Section: Associations Between Metacognition and Eating Disorder Symptomssupporting
confidence: 93%
See 1 more Smart Citation
“…This puts our findings in line with previous research, having found that worry and rumination are associated with eating disorder symptoms (Startup et al, 2013;Sternheim et al, 2012). Earlier studies have shown that eating disorder symptoms correlated significantly with worry (Sternheim et al, 2012), and rumination (Startup et al, 2013).…”
Section: Associations Between Metacognition and Eating Disorder Symptomssupporting
confidence: 93%
“…A positive correlation was found between worry and eating disorder symptomatology. Startup et al (2013) also found elevated scores on measures of worry and rumination in a sample of 62 patients with AN compared to healthy controls. Additionally, they also found a positive correlation for both worry and rumination related to eating disorder symptoms, and that worry and rumination predicted severity of the eating disorder over and above measures of mood.…”
Section: Metacognition In Eating Disordersmentioning
confidence: 76%
“…Yet, by applying concentration to perceived 'controllable' aspects of one's situation (calorie intake, weight) such cognitive processes could also be argued to represent cognitive avoidance. They maintain a narrow cognitive focus to avoid thinking about other 'unmanageable' difficulties (Startup et al, 2013). This could not be captured by the measures used in the studies herein and therefore the degree of cognitive avoidance may not be accurately assessed; hence requires further investigation.…”
Section: Integration Of Findings With Previous Researchmentioning
confidence: 95%
“…This idea is particularly applicable to anorexia nervosa (AN), a devastating condition with the highest mortality rate of any psychiatric illness (Harris and Barraclough, 1998). AN is associated with somatic preoccupation with visceral gut sensations (eg, fullness; Perez et al, 2013), as well as heightened fear and anxious rumination (Frank et al, 2012;Startup et al, 2013), and enduring anxiety-related personality traits such as harm avoidance (Brewerton et al, 1993;Fassino et al, 2002). Because of this, influential theoretical accounts about the neurobiology of AN have recently highlighted the likely role of interoceptive regions in the insula in the pathophysiology of the disorder (Kaye et al, 2009(Kaye et al, , 2013Nunn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%